Malígny fibrózny histiocytóm ako raritná príčina akútnej končatinovej ischémie - Pobehová, J; Zavacká, M; Závacký, P; Pobeha, P; Koščo, M; Frankovičová, M (Rozhledy v chirurgii, 2017)
Malignant fibrous histiocytoma (MFH) represents a rare malignant affection of heart and aorta. Its clinical presentation depends on the localisation, size, degree of invasion and metastasis. Previously, relatively few cases of acute tumour mass embolisation into the visceral and limb arterial system were described in the literature. In the present case study we describe a case of acute ischemia of both lower extremities caused by thromboembolic mass of MFH cells. According to literary sources this tumour type is characterized by poor prognosis as it was in the case of our patient.
Keywords: Ischemia; acute limb ischemia peripheral embolisation Fogarty embolectomy malignant fibrous histiocytoma.; Humans; Histiocytoma, Malignant Fibrous; lidé; maligní fibrózní histiocytom; ischemie